Plasma‐assisted deposition of iron oxide thin films for photoelectrochemical water splitting. Issue 1 (12th August 2020) - Bosso, Piera; Milella, Antonella; Barucca, Gianni; Mengucci, Paolo; Armenise, Vincenza; Fanelli, Fiorenza; Giannuzzi, Roberto; Maiorano, Vincenzo; Fracassi, Francesco
Abstract: Iron oxide thin films for photoelectrochemical (PEC) water splitting were deposited by radiofrequency sputtering of an iron target in argon/oxygen plasma mixtures, followed by thermal annealing. The chemical composition and structure of deposited film can be tuned by controlling the gas feed composition and the annealing temperature. The thermal treatment extensively improves the PEC water splitting performances of the films deposited at the lowest O2 percentages (0–1%), allowing to obtain photocurrent densities up to 1.20 mA/cm 2 at 1.23 VRHE . Increasing the oxygen percentage in the plasma feed allows the direct growth of photoactive films; the best result is found for the hematite film produced at 50% O2, characterized by a photocurrent density of 0.21 at 1.23 VRHE . Abstract : Iron oxide thin films were prepared by radiofrequency sputtering deposition and tested as photoanodes for water splitting. Film composition and structure are tailored by O2 /Ar ratio and by postdeposition annealing temperature. Photocurrent densities up to 1.20 mA/cm 2 at 1.23 VRHE could be obtained. Photoactive hematite could be also directly grown in plasma without thermal annealing, though with reduced performances.